Dlaczego Cyprian Kamil Norwid przeciął pamiątkowy rysunek z Egiptu od Juliusza Słowackiego ? O prywatności w Czarnych Kwiatach - Szczeglacka-Pawłowska, Ewa (Colloquia Litteraria, 2014)
Why Cyprian Norwid tore a souvenir drawing from Egypt from Juliusz Słowacki? The article treats of the issues of privacy and informality in Cyprian Norwid’s Czarne kwiaty [Black Flowers]. The poet wrote about events from the lives of individuals whose status was public. He wrote, among others, about informal meetings, universalising their meaning. He published the piece in a monthly insert to Czas daily newspaper. A question arises whether Norwid had the right to unveil the privacy of these people. Did he ask them to let him exploit very private moments from their lives? A scene from the drama, where the narrator (the author of Czarne kwiaty) cuts a souvenir drawing from Juliusz Słowacki – he sends one half to Poland and keeps the other to himself – reveals the quintessence of the piece. By cutting the drawing from Egypt Norwid made it into two pieces; at the same time he destroyed a souvenir from Słowacki and, in a certain sense, those things that were the most private in relationships with particular people.